Wearable Carbon Nanotube‐Spandex Textile Yarns for Knee Flexion Monitoring. Issue 1 (4th December 2022) - Fay, Cormac D.; Mannering, Nicholas; Jeiranikhameneh, Ali; Mokhtari, Fatemeh; Foroughi, Javad; Baughman, Ray H.; Choong, Peter F. M.; Wallace, Gordon G.
Abstract: Carbon nanotube‐spandex textiles are rapidly gaining in popularity as sensors for human motion, yet their use as—and comparison to—viable clinical‐based instrumentation has not been thoroughly investigated. Herein, the use of novel yarn‐based sensors that show excellent characteristics, ideal for joint kinematic sensing, is described. Knee kinematic monitoring of nine healthy participants while walking on a treadmill is examined. This is enabled through a 3D‐printed knee brace integrated with a wireless transmission device. The design, development, and testing of the wearable device is presented along with wireless data capture and processing. Additionally, the findings are compared in vivo to those reported by a reference optoelectronic measurement system (KneeKG) for validation purposes. The results show a high correlation between both systems, with an average Pearson's r ‐value of 0.89 across each corresponding knee. This study is the first to explore the use of these novel yarn sensors for sagittal knee kinematic monitoring on participants during trials and validate the findings via an optoelectronic measurement system. Abstract : The Knee Flexion Monitor presents a clinically viable cost‐effective sensing system capable of wirelessly monitoring knee flexion of participants. The thread‐based system is made of carbon nanotubes and spandex, which is used in conjunction with a 3D‐printed knee brace. The results from nine participants are compared to a reference instrument and shows excellent fidelity.